2013
DOI: 10.1007/s00345-013-1179-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of solifenacin in men with overactive bladder: results of an observational study

Abstract: Introduction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…The majority of patients reported that solifenacin therapy was beneficial and produced satisfactory outcomes. These results are consistent with previous reports that have demonstrated that solifenacin therapy significantly improves all objective and subjective OAB symptoms .…”
Section: Discussionsupporting
confidence: 93%
“…The majority of patients reported that solifenacin therapy was beneficial and produced satisfactory outcomes. These results are consistent with previous reports that have demonstrated that solifenacin therapy significantly improves all objective and subjective OAB symptoms .…”
Section: Discussionsupporting
confidence: 93%
“…to be good at central nervous system penetration in an in vivo study, but some clinical studies suggested that it is not significantly related to cognitive function [17]. Rather, one study suggested that patients taking donepezil for Alzheimer's disease can use it safely without deteriorating their cognitive function [18].…”
Section: Discussionmentioning
confidence: 99%
“…Post hoc analyses of data failed to reveal any relationship between age, sex, MMSE total score at baseline vs. total score at week 12, or higher dose of solifenacin and change in cognitive function. Results of a large observational study with an all-male cohort (mean age 67 years) taking solifenacin for relief of OAB symptoms also reported no change in cognitive function after 12 weeks using the MMSE [30] . Using a more sensitive tool for assessing cognitive function, 2 separate studies found no evidence of impairment in cognitive function in healthy elderly volunteers [31] and similar effects to placebo in cognitive outcomes in elderly volunteers with mild cogni- Hampel [34] .…”
Section: Discussionmentioning
confidence: 99%